Cost-effectiveness of self-sampling and enhanced strategies for HPV prevention among men who have sex with men in China: a modeling study - Zhen-Hao Wu; Yu-Jing An; Zhen-Xing Chu; Xin-Ru Li; An-Yang Hou; Yong-Jun Jiang; Qing-Hai Hu (BMC Medicine)
Abstract Background Human papillomavirus (HPV) testing on self-collected samples (self-sampling) can address the challenges with facility-sampling among men who have sex with men (MSM). However, its cost-effectiveness and effective combination with vaccination must be evaluated, particularly in the absence of national HPV vaccination immunization programs among men. Methods We constructed a decision-analytic Markov model to assess the cost-effectiveness of the status quo, HPV self-sampling at different intervals, vaccination alone, and HPV self-sampling–vaccination combination based on the incremental cost-effectiveness ratio (ICER), from a healthcare system perspective. Univariate and probabilistic sensitivity analyses were conducted to evaluate the robustness of the proposed model. Results A lifetime cost-effectiveness analysis on a hypothetical cohort comprising 100,000 MSM aged 12 years at baseline projected that combining screening and vaccination generated incremental costs of US$49,638–219,213 million while accruing 189,881–271,564 quality-adjusted life-years (QALYs) compared with the status quo. Incorporating HPV self-sampling significantly improved the cost-effectiveness of traditional interventions. Remarkably, combining annual HPV self-sampling with nine-valent vaccination proved the most cost-effective at a willingness-to-pay (WTP) threshold three times the Chinese per-capita gross domestic product (GDP). This strategy yielded an ICER of $775 per QALY compared to the status quo and was 55.7% possible to be cost-effective with a WTP threshold three times the per-capita GDP, outperforming other strategies. Conclusions Implementing annual HPV self-sampling along with nine-valent vaccination is projected to be the most cost-effective among MSM in China. Reducing the costs of HPV self-sampling and vaccination is crucial for guaranteeing that future initiatives produce favorable economic outcomes. These findings provide valuable guidance for formulating policies on HPV prevention among MSM in China.